Postnatal Depression Is a Public Health Nursing Issue: Perspectives from Norway and Ireland - Kari Glavin; Patricia Leahy-Warren (Nursing Research and Practice)
The framework provided by the Millennium Development Goals includes maternal health as an area of priority. Postnatal depression (PND) is a serious public health issue because it occurs at a crucial time in a mothers’ life, can persist for long periods, and can have adverse effects on partners and the emotional, behavioural, and cognitive development of infants and children. Internationally, public health nurses (PHNs) are key professionals in the delivery of health care to mothers in the postpartum period, and international research collaborations are encouraged. Two researchers from the European Academy of Nursing Science (EANS) identified a need to collaborate and strengthen research capacity and discussion on postnatal depression, a public health nursing issue in both countries. Within the context of public health and public health nursing in Ireland and Norway, the aim of this paper is to present a discussion on the concept of PND, prevalence, and outcomes; screening issues for PHNs; and the research evidence of the benefits of social support in facilitating recovery for new mothers.